ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA PT. INDOFOOD SUKSES MAKMUR TBK. - Rohman, Edy (STAI Denpasar Bali, 2023)
Financial reports report the activities carried out by the Company in an accounting period. The activities carried out are expressed in the form of numbers. The numbers in the financial statements become less meaningful if seen only from one side, the numbers in the financial reports can be more meaningful in assessing the performance of a company if they can be compared between one accounting post and another accounting post in the financial report which is called financial ratios. The purpose of this research is to find out how the financial performance of PT. Indofood Sukses Makmur, Tbk. based on financial ratio analysis consisting of liquidity, solvency and profitability ratios. The data analysis method used is a quantitative descriptive method using measurements of liquidity, solvency and profitability ratios. Based on the overall liquidity ratio, the company is in good condition and tends not to be able to maximize its working capital, which is indicated by the high liquidity ratio in 2022. Based on the profitability ratio, it is known that the company's funding structure tends to be balanced between funding sources from third parties and the company owner. The higher the solvency ratio, the higher the company's risk of default. In 2022, the company seeks to reduce its solvency ratio which is already quite high. Based on the profitability ratio, the company's performance can be said to be fluctuating, especially in 2022, there will be a decline in the company's profitability. This can be caused by the lack of optimal use of the company's resources to achieve profits.